THE CRITICAL CONNECTION BETWEEN ORAL HEALTH AND CARDIOVASCULAR WELL-BEING - Silva, Suzana Carolina Ramos (Revista Sistemática, 2024)
The relationship between oral health and cardiovascular health has gained significant attention, particularly regarding the prevention of periodontal diseases to mitigate cardiovascular complications, especially in hypertensive patients. Periodontal diseases, including gingivitis and periodontitis, are chronic infections affecting the gums and supporting structures of teeth, potentially leading to systemic inflammation and the release of inflammatory mediators into the bloodstream. This chronic inflammation is associated with cardiovascular diseases, as it can contribute to plaque formation in arteries, increasing the risk of adverse cardiac events. Hypertension is a notable risk factor for cardiovascular diseases, and studies suggest that individuals with periodontal diseases are more likely to develop hypertension and related conditions. Therefore, proper prevention and treatment of periodontal diseases play a crucial role in the cardiovascular health of hypertensive patients. Early detection and intervention through periodontal screening programs can help reduce systemic inflammation and healthcare costs related to cardiovascular complications. Various studies support the positive effects of periodontal therapy on cardiovascular risk factors, indicating significant reductions in blood pressure and inflammatory markers following periodontal treatment. Furthermore, the alarming prevalence of hypertension, affecting approximately 45% of the global population, necessitates increased awareness of its links to periodontal health. Collaborative approaches between dentists and primary care physicians are essential to improve early detection and management of both periodontal and systemic health issues. Investing in preventive dental care not only enhances oral health but can also lead to substantial savings in healthcare costs by alleviating the financial burden associated with treating cardiovascular diseases. Ultimately, integrating oral health into broader health strategies is vital for promoting overall health and preventing chronic diseases.